Exosomal MicroRNAs: Biomarkers of moyamoya disease and involvement in vascular cytoskeleton reconstruction - Wang, Mengjie; Zhang, Bin; Jin, Feng; Li, Genhua; Cui, Changmeng; Feng, Song (Heliyon, 2024)
Moyamoya disease currently lacks a suitable method for early clinical screening.This study aimed to identify a simple and feasible clinical screening index by investigating microRNAs carried by peripheral blood exosomes. Experimental subjects participated in venous blood collection, and exosomes were isolated using Exquick-related technology. Sequencing was performed on the extracted exosomal ribonucleic acids (RNAs) to identify differential microRNAs. Verification of the results involved selecting relevant samples from the genetic database. The study successfully pinpointed a potential marker for early screening, hsa-miR-328-3p + hsa-miR-200c-3p carried by peripheral blood exosomes. Enrichment analysis of target genes revealed associations with intercellular junctions, impaired cytoskeletal regulation, and increased fibroblast proliferation, leading to bilateral internal carotid artery neointimal expansion and progressive stenosis. These findings establish the diagnostic value of hsa-miR-328-3p+hsa-miR-200c-3p in screening moyamoya disease, while also contributing to a deeper understanding of its underlying pathophysiology. Significant differences in microRNA expressions derived from peripheral blood exosomes were observed between moyamoya disease patients and control subjects. Consequently, the utilization of peripheral blood exosomes, specifically hsa-miR-328-3p + hsa-miR-200c-3p, holds potential for diagnostic screening purposes.